Ober Verteilung der Basiselementen in den freien Zahlenhalbgruppen. II - Cibulskytė, A. (Lithuanian Mathematical Journal, 1970)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:А. Цибульските. О распределении образующих элементов в свободных числовых полугруппах. IID. Cibulskytė. Laisvos skaitinės pusgrupės generuojančių elementų pasiskirstymo klausimu. II